Testing the Weak-Form Efficient Market Hypothesis in Selected Central and Eastern European Markets - Bedenik, Timotej; Oplotnik, Žan Jan (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper presents the results of testing the weak form of the Efficient Market Hypothesis (EMH) for the stock indices of Poland, Hungary, the Czech Republic, Slovakia, Slovenia, and Croatia using daily data for 2015–2024. The sample is split into two subperiods- 2015–2019 and 2020–2024 - with the cut at 1 January 2020 to capture the impact of the COVID-19 crisis on observed efficiency. The tests employed are the Lo–MacKinlay variance-ratio test, unit-root tests (ADF, Phillips–Perron), and serial-dependence tests (Ljung–Box Q and the runs test). For the full period, results are heterogeneous: the WIG (Poland) and BUX (Hungary) indices, on average, exhibit properties consistent with weak-form EMH, whereas the SAX (Slovakia) generally does not; the remaining indices display partial violations. After 2020, evidence in favour of weak-form efficiency declines noticeably for most indices, with outcomes varying in part by the test used.